Markering och ordboksstruktur - Svensén, Bo (LexicoNordica, 2000)
This contribution deals with some structural aspects of diasystematic marking in dictionaries. The functions and structural properties of the markers themselves are di scussed as well as their relationship to other textual elements and to each other, applying a slightly extended version of the conceptual and terminological framework used in Nordisk leksikografisk ordbok [Nordic Dictionary of Lexicography]. Some problems pertaining to the user aspect are also touched upon.